Peningkatan Efisiensi Material dan Reduksi Limbah Beton Melalui Integrasi Lean Construction pada Proyek Konstruksi Masjid X di Desa Banjarejo - Adinda Khusnul Khotimah; Sony Susanto (Jurnal Talenta Sipil, 2026)
Concrete waste is one of the main challenges in construction projects with relatively high levels of waste. The level of waste in construction can reach 5–15%, leading to increased costs, delays, and negative environmental impacts.. This study evaluates the effectiveness of implementing Lean Construction—including Value Stream Mapping (VSM), Just-In-Time (JIT), and Continuous Improvement (Kaizen)—in controlling concrete waste in the construction project of Mosque X in Banjarejo Village, Indonesia. Data on planned, used, and installed concrete volumes were collected for five main structural elements and then analyzed quantitatively. The results show that concrete waste can be reduced to 2.25%, well below the industry tolerance limit of 5%, with a Waste Reduction Efficiency (WRE) of 97.8%. Workflow efficiency increased by up to 80% through VSM, material delivery achieved 100% accuracy with JIT, and Kaizen reduced labor idle time by more than 30%. These findings not only reinforce the theoretical contribution of Lean Construction but also produce a practical material management model that can be adopted in similar projects in Indonesia to improve efficiency, sustainability, and construction waste mitigation.